2017
DOI: 10.4103/ijmpo.ijmpo_43_16
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma presenting as thyroid plasmacytoma

Abstract: Thyroid gland and thyroid cartilage infiltration in multiple myeloma (MM) are rare. Here, we discuss a patient who presented with hoarseness of voice and was found to have a hypodense lesion in right lobe of thyroid involving thyroid and cricoid cartilage. Fine-needle aspiration cytology with immunohistochemistry revealed extramedullary plasmacytoma of thyroid. MM was ruled out initially by serum protein electrophoresis, immunofixation, and bone marrow biopsy. Later, lytic lesions were found in multiple bones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The electronic searches yielded 1143 articles (PubMed: 418, Web of Science: 292, Embase: 265, and Scopus: 168) and 82 studies reporting 102 individuals were included in this systematic review 17–98 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic searches yielded 1143 articles (PubMed: 418, Web of Science: 292, Embase: 265, and Scopus: 168) and 82 studies reporting 102 individuals were included in this systematic review 17–98 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review identified concordance rates higher than 64% for the smear and 77% for the cell‐block technique regarding diagnostic capability for the evaluation of intraosseous jaw lesions, including malignant lesions 16 . Despite several published reports on the cytopathological diagnosis of PCN, either in isolated manifestations (extramedullary or solitary bone plasmacytoma) or as a consequence of PCM, 17–98 there is a lack of compiled information investigating the agreement of cytopathological and histopathological findings, along with others ancillary cytological methods such as smears and cell blocks. In fact, FNAC represents a faster, cheaper and more diversified noninvasive diagnostic approach.…”
Section: Introductionmentioning
confidence: 99%
“…EMP/plasma cell infiltration of thyroid in cases of MM is very rarely reported in literature and only countable cases are reported on FNAC . An elderly patient with a thyroid swelling and lytic bony lesion is almost always suggestive of follicular carcinoma with bone metastasis or an incidental benign thyroid swelling with bone metastasis of some unknown visceral malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy of the thyroid gland was refused by the patient. Cases of multiple myeloma associated with plasmacytoma in thyroid gland have been reported 14,15…”
Section: Discussionmentioning
confidence: 99%